Achieving patient satisfaction in a high stress health environment - Callender, Guy; Meunier, C.; Rebolar-Lazaro, I. (EBSCO Publishing, 2011)
The development of in vitro fertilisation (IVF) has created a new branch of medical science that has the potential to bring great happiness to those who achieve successful pregnancies and long periods of misery to those who are unsuccessful. As a part of some wider research into the support needs of clients, this paper addresses some of the challenges of managing patient satisfaction in an area of health sciences that is associated with high levels of patient uncertainty and also high aspiration for positive outcomes. The authors have used the literature of the business sector, especially retailing and marketing, to explore the key parameters of patient satisfaction and the outcomes have relevance for both medical practice and customer service.